Assessing the impact of the public nutrition information environment: Adapting the cancer information overload scale to measure diet information overload. Issue 1 (January 2019) - Ramondt, Steven; Ramírez, A. Susana
Highlights: Contradictory information can lead to beliefs that may affect health behavior. The cancer information overload scale was adapted to diet information overload. Nutrition education should consider the contradictory information environment. Abstract: Objective: A growing body of research suggests that exposure to too much information – particularly contradictory information that characterizes much health-related information – can lead to feeling overwhelmed. This construct has been conflated with fatalistic beliefs that are negatively associated with preventive behaviors. The objective of this study was to adapt the 8-item Cancer Information Overload (CIO) scale to assess overload of healthy diet information. Methods: Confirmatory factor analyses with a community sample of rural California adults (n = 290; 75% female; 58% Latino; 46% ≤ H.S./G.E.D.). Results: Items assessing Diet Information Overload loaded significantly on their relevant factor; factor loadings were acceptable (β > .40). The adapted original scale (CFI = 1.000, RSMEA = .000, SMSR = .022) and a shorter 5-item scale (CFI = .984, RMSEA = .051, SMSR = .026) fit well. Conclusion: The Cancer Information Overload scale was successfully adapted and shortened to measure perceptions – previously mischaracterized as fatalistic – pertaining to diet information. Improved measures distinguishing between fatalistic beliefs and outcomes of the information environment are critical. Practice Implications: Understanding information overload is important for shaping prevention messages distinct from those needed to address fatalistic beliefs. Nutrition education efforts should consider the broader – cluttered – information environment in which nutrition education and communication occurs, and public health messages may drown.